Implementation of Integrated Pilot Training Setup (IPTS) - J. K. Rahul Jayawardana (New Visions in Science and Technology Vol. 7, 2021)
Civil aviation is the most frequently utilised kind of transportation in the modern world, with millions of people using it every year all over the world. Since the beginning of the twentieth century, civil aviation has evolved in a vast process to provide efficient, effective, and safer transportation means to humans. However, despite the fact that aviation has become the safest mode of transportation, aviation-related accidents and crashes are fatal and more disastrous than any other mode of transportation. When considering air crashes, it becomes clear that pilot mistake plays a key part in large disasters that can result in the loss of hundreds of lives and property. In this study, the emphasis was placed on pilot training for a specific aircraft and how to make them confident and skilled while operating it. As a result, this paper is produced to provide the IPTS technique, which has the qualities of successfully and efficiently teaching pilots. Finally, the IPTS general method was provided, along with information on each stage.